Public Stigmatization of Women Victims of Intimate Partner Violence by Professionals Working in the Judicial System and Law Enforcement Agencies in Spain - Murvartian, Lara (Journal of interpersonal violence, 2023)
Recent international literature has demonstrated that the public stigma suffered by women victims of intimate partner violence (IPV) makes them less likely to disclose the abuse and to seek help and has a negative influence on third-party responses, with professionals working in the judicial system and law enforcement agencies being particularly susceptible to its impact. The absence of theories explaining how this stigma works and the legal and cultural differences that exist between countries prompted us to explore the process by which professionals working in law enforcement and the judicial system in Spain stigmatize this specific group of victims. Constructivist grounded theory was used to establish meanings and relationships between the components and processes involved in stigmatization, based on the data collected from individual, semi-structured, in-depth interviews with 11 professionals working in the aforementioned fields. In addition to the stigmatization that the interviewees claimed to have observed in coworkers, we also analyzed the conscious and/or unconscious stigmatization that they themselves exercised, which became evident during the course of the interview. The results confirmed the existence of stigma among professionals, with the said stigma often being unintentional and implicit in nature. The theoretical model that emerged from the data comprised four broad categories linked to the origin of the stigma, stigmatizing myths about victims and IPV, stigmatizing responses to victims who are seeking help, and the consequences of the stigma for the victims. In the study, we outline the associations observed between these factors and the subcategories included in each, and highlight the need to design training programs for professionals who are designed to fight against the stigma and which include self-analysis exercises as well as theoretical contents. We also discuss other implications of the results for both research and practice.